(untitled) (Academia Science Repository, 2023)
This article will review and review the methods of teaching the Russian language. When teaching Russian at the Faculty of Finance, certain methods can be used to provide students with a deeper understanding of the terminology and concepts specific to the field. Through vocabulary training, a special terminology used in finance, teachers can focus on building students’ vocabulary in the field.